UPDATE ON ORAL AND TOPICAL THERAPY FOR MELASMA IN REPRODUCTIVE AGE: A LITERATURE REVIEW - DEWI, MEYLIA ARINDA CANDRA; AZAHRA, MIRANDA; PRAKOESWA, FLORA RAMONA SIGIT; PRAMUNINGTYAS, RATIH (International Journal of Applied Pharmaceutics, 2025)
Melasma is a common pigmentation disorder often seen in women of reproductive age with Fitzpatrick skin types IV-VI, characterized by symmetrical hyperpigmented patches on the face. Major factors influencing melasma include UltraViolet (UV) exposure, genetic predisposition, and hormonal changes. This condition can significantly impact patients' quality of life, thus requiring effective and safe therapeutic approaches. This study aims to evaluate the effectiveness and safety of various melasma treatments, both topical and systemic, based on the latest literature review. This research uses a literature review design with a PICO (Patient, Intervention, Comparison, Outcome) approach to select articles from PubMed and ScienceDirect databases. Articles analyzed include studies published in the last 5 years, written in English, and involving patients with melasma. Various treatments for melasma, such as hydroquinone, Triple Combination Cream (TCC), tranexamic acid, vitamin D, and natural-based treatments, show effectiveness in reducing the severity of melasma. Mild side effects were reported for some treatments, such as irritation with hydroquinone or mild gastrointestinal disturbances with oral tranexamic acid. Each treatment has advantages in specific contexts, depending on the patient's needs and characteristics. All therapies evaluated show positive results with varying degrees of effectiveness. Treatment selection should consider the severity of melasma, patient tolerance to the medication, and potential side effects. An individualized approach and combination therapy can be adapted to optimally meet patient needs.